IMPLEMENTASI KEBIJAKAN AGRARIA DAN TATA RUANG/BADAN PERTANAHAN NASIONAL DALAM PENYELESAIAN SENGKETA TANAH DI KABUPATEN SIDENRENG RAPPANG - Armi, Muhammad Nurdzaky; Syarifuddin, Haeruddin; Yasin, Akhmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to describe and analyze the implementation of policies by the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN) in resolving land disputes in Sidenreng Rappang Regency. This research uses a descriptive qualitative approach with purposive sampling techniques to determine relevant informants. The results indicate that the policy implementation is carried out through administrative and non-litigation approaches such as mediation and deliberation, supported by the digitalization of land data programs. The effectiveness of policy implementation is influenced by communication, human resources, implementers’ attitudes, and bureaucratic structure. Despite positive efforts, land dispute resolution still faces obstacles, such as weak interagency coordination and suboptimal public outreach. Therefore, a more integrative and participatory implementation strategy is needed to strengthen legal certainty and reduce agrarian conflict potential in the region